THE ROLE OF CRITICISM IN THE DEVELOPMENT OF THE ARABIC LANGUAGE IN ANCIENT TIMES - Ghafel Fatna (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
Literary criticism has contributed to preserving the Arabic language and elevating it to its proper position through criticism of literary texts, poetry or verse, which contributed to the development of the language of the Qur’an. so critics had to beware of the weakness of the language. A group of linguists and critics confronted this danger and codified the language and made it controls that protect it from any weakness.this led to the emergence of specialized schools of thought.In this research paper,we will attempt to understand the role of criticism in developing and serving the Arabic language.